Relationship Between LAPTM4B Gene Polymorphism and Susceptibility of Malignant Melanoma in Chinese Patients - Zhang, Meng (Neoplasia Press, 2014)
Lysosomal-associated protein transmembrane 4 beta (LAPTM4B) is known as an oncogene associated with many human malignant tumors. There are two alleles of the gene, LAPTM4B*1 and LAPTM4B*2. Previous studies have shown that LAPTM4B polymorphism contributes to the risk of many cancers. This case-control study was to investigate the relationship between LAPTM4B gene polymorphism and susceptibility of malignant melanoma. The genotypes of LAPTM4B were determined in 617 control subjects and 220 patients with malignant melanoma by utilizing polymerase chain reaction based on specific primers. The genotypic distribution of LAPTM4B and Hardy–Weinberg equilibrium were analyzed by χ2 test. Odds ratio and 95% confidence interval was calculated by unconditional logistic regression. The distributions of LAPTM4B genotypes were significantly different between melanoma patients (45.9% for *1/1, 46.4% for *1/2 and 7.7 for *2/2) and controls (54.5% for *1/1, 39.9% for *1/2 and 5.7 for *2/2). LAPTM4B *1/2 and LAPTM4B *2/2 had a 1.396-fold and 1.619-fold higher risk for melanoma occurrence than *1/1, and subjects with LAPTM4B*2 have a 1.308-fold higher risk than LAPTM4B*1 carriers. No association between LAPTM4B genotypes and gender, age, subtype, Clark level of invasion, Breslow thickness, ulceration, clinical stage, and C-KIT, BRAF gene mutation status was observed. LAPTM4B*2 is associated with the high risk of malignant melanoma and carrying LAPTM4B *2 may be a susceptible factor to Chinese melanoma patients.